Video Watermarking Techniques Classifications And Applications - Swaraja. K; Meenakshi.K; Padmavathi.K; Ch. Ushakumari; G.Karuna (International Journal of Psychosocial Rehabilitation, 2020)
Digital watermarking is a scheme that involves in concealing the information within the signal which is translucent to the user. Video Watermarking is one among the inspiring fields to ensure the improvement of the system by facilitating the authentication of data, advertisement surveillance, safety, tracing of piracy and copyright protection procedures for digital media, concealed within dynamic video codec. Digital watermarking technology is being adopted to ensure and facilitate data authentication, safety and copyright protection of digital media. It is contemplated as the most significant technology in the modernized world, to avert illegal replication of data. Digital watermarking can be practiced on multimedia data. In this work, we emphasized particularly on the overview of different domains in video watermarking schemes, along with its definitions, properties, applications and evaluation constraints utilized to expand the security of data